Tinjauan Kenyamanan Termal pada Rumah Tradisional Aceh - Raudhatul Jannah; Marlisa Rahmi; Riza Aulia Putra (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research reviews thermal comfort in the aspects of ventilation and lighting in Aceh Houses in Pidie Regency, based on residents' perceptions. Acehnese houses, as traditional architecture, have natural and artificial ventilation and lighting systems that are considered adequate. This research uses a qualitative approach with a case study method, involving field observations, interviews, and documentation in five sub-districts: Mutiara, Mutiara Timur, Glumpang Tiga, Peukan Baro, and Delima. Next, the data col-lected will be analyzed descriptively using coding.